E-HRM Attributes and Internal Stakeholders' Satisfaction: A Quantitative Study in Select Indian Organizations - Sinha, Bhagawan Chandra; Mishra, Mridula (Prabandhan: Indian Journal of Management, 2015)
In the present times, businesses have a lot of stakeholders, but the internal stakeholder, that is, the employees are the most important stakeholders as they are the deciding factor and determine the direction and level of success a business attains, especially in a knowledge economy, where services are high in demand. A higher satisfaction level of an employee does not guarantee high level of performance, but is desirable for an organization to remain competitive in business. Some organizations proactively, and few with the rapid development of e-commerce and significant rise of the virtual, networked organizations, have compelled HR professionals to sail in the digital world and offer services on an electronic platform, resulting in the emergence of the electronic human resource management (e-HRM). E-HRM is an integration of information and communication technology (ICT) and HR mechanism, content, and processes to provide services to different stakeholders and simultaneously provides a competitive edge to the organization. There are several e-HRM attributes which determine the satisfaction level of an employee. To measure the present level of e-HRM attributes and also to examine a difference in the level of e-HRM attributes based on employees' demographic variables, and increase in internal stakeholders' satisfaction, a questionnaire was formulated, and responses were sought from operatives, supervisors, and managers of selected Indian organizations and one-sample t-test, one way ANOVA, and regression analysis were used respectively as a statistical tool of measurement in the present study.